ANALYSIS OF AFFECTING FACTORS TO THE OF QUALITY LIFE PATIENTS WITH TYPE 2 DIABETES MELLITUS AT HOSPITAL IN MAKASSAR - Hadju, Novaldi; Muhammad Syafar; Eha Sumantri (Indonesia Epidemiological Journal, 2024)
Background: Diabetes mellitus is a chronic disease that cannot be completely cured and is one of the factors that affecting the quality of life of patients. The prevalence of diabetes mellitus from the 2018 Riskesdas results increased to 2%, in South Sulawesi 1.6%, Makassar 2.5%. The purpose of research was to analyze the factors affecting quality of life of patients with type 2 diabetes mellitus at hospital in Makassar. Methods. This type of research used is descriptive analytic with cross-sectional approach with a sample of 54 patients. The sampling technique is accidental sampling.Collecting data by interview with a questionnaire from diabetesquality of life revised version (DQoL) and analyzed based on thechi-square test and multiple logistic regression test. Results. Of the 54 patients, 70.4% had a high quality of life and 29.6% had a low quality of life. There was a significant effect between knowledge variables (0.040), duration of diabetes (0.043), and gangrene (0.001). Gangrene variable has the most influence on the quality of life of patients with type 2 diabetes mellitus (multivariate analysis results = 0.005). Conclusions. Knowledge, duration of diabetes, andgangrene have an affecting on the quality of life of patients withtype 2 diabetes mellitus in RSUD Labuang Baji Makassar. Suggested for health workers to improve socialization and educationto patients about the illness involving the patient's family.